2022
DOI: 10.1186/s40814-022-01193-y
|View full text |Cite
|
Sign up to set email alerts
|

Auditory rhythmical cueing to improve gait in community-dwelling stroke survivors (ACTIVATE): a pilot randomised controlled trial

Abstract: Background Gait impairment limiting mobility and restricting activities is common after stroke. Auditory rhythmical cueing (ARC) uses a metronome beat delivered during exercise to train stepping and early work reports gait improvements. This study aimed to establish the feasibility of a full scale multicentre randomised controlled trial to evaluate an ARC gait and balance training programme for use by stroke survivors in the home and outdoors. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The results of the study female college students after exercise intervention, the balance area of the test group increased substantially, and the control group decreased slightly, proving that exercise is important for enhancing the balance ability of female college students. Studies have demonstrated that exercise is beneficial in improving functional capacity and dynamic balance in children with hemiplegia (Soliman et al, 2022), a randomized controlled trial showed that a gait training program used by stroke patients was beneficial in improving balance (Shaw et al, 2022), and another study female university students through 8 weeks of fitness qigong exercises. The result was a significant increase in balance test scores post-intervention compared to pre-intervention scores (Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study female college students after exercise intervention, the balance area of the test group increased substantially, and the control group decreased slightly, proving that exercise is important for enhancing the balance ability of female college students. Studies have demonstrated that exercise is beneficial in improving functional capacity and dynamic balance in children with hemiplegia (Soliman et al, 2022), a randomized controlled trial showed that a gait training program used by stroke patients was beneficial in improving balance (Shaw et al, 2022), and another study female university students through 8 weeks of fitness qigong exercises. The result was a significant increase in balance test scores post-intervention compared to pre-intervention scores (Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participants were required to have a Mini-Mental State Examination (MMSE) score greater than 24 and a Modified Ashworth Scale grade of 1 or 1+ to qualify for the study (17,21). Conversely, individuals presenting with dementia, depression, productive psychosis, visual and auditory impairments, foot drop, or a history of recurrent transient ischemic attacks (TIA) were systematically excluded from participation (18). Data collection commenced with the acquisition of demographic information from each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Techniques such as acoustic cueing through metronomes have shown promise in improving walking cadence, speed, symmetry, and stride length, with both immediate and lasting effects (17). Auditory rhythmic cueing (ARC) and cadence retraining with audio or visual feedback are among the strategies employed to facilitate gait rehabilitation (18,19). The imperative to enhance the quality of life for individuals with hemiplegia through effective intervention strategies is clear.…”
Section: Introductionmentioning
confidence: 99%